2022
DOI: 10.3390/buildings12060785
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring of a Brazilian Concrete Bridge for Estimating Specific Dynamic Responses

Abstract: A 3D coupled model to simulate vehicle–bridge interactions (VBI) to estimate its structural responses and impact factors (IMs) was developed in this study. By structural health monitoring (SHM) of a real concrete bridge, several data were collected to calibrate the bridge model by the finite element method (FEM). These models provide the bridge response in terms of vertical displacements and accelerations. VBI models provide reliable outputs without significantly altering the dynamic properties of the bridge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The authors concluded that, for pavement with poor surface conditions, AASHTO [5] may underestimate the dynamic amplification effects. Some authors, including Oliva et al [6][7][8], performed an analysis of the roughness influence in terms of dynamic amplification values in a simply supported bridge and in a three-span continuous bridge. In this regard, the results demonstrated that the dynamic response was overestimated when the differences between the left and right roughness profiles were neglected in the case of 3D models with two profile lines corresponding to the vehicle circulation lines.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that, for pavement with poor surface conditions, AASHTO [5] may underestimate the dynamic amplification effects. Some authors, including Oliva et al [6][7][8], performed an analysis of the roughness influence in terms of dynamic amplification values in a simply supported bridge and in a three-span continuous bridge. In this regard, the results demonstrated that the dynamic response was overestimated when the differences between the left and right roughness profiles were neglected in the case of 3D models with two profile lines corresponding to the vehicle circulation lines.…”
Section: Introductionmentioning
confidence: 99%